1994
DOI: 10.1007/bf00207475
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of growth hormone and thyroid-stimulating hormone in patients with dementia

Abstract: We studied the growth hormone (GH) response to GH-releasing hormone (GHRH) and the thyroid-stimulating hormone (TSH) response to thyrotropin-releasing hormone (TRH) in four groups of patients with dementia and examined whether GH and TSH secretion is altered in patients with Alzheimer's disease. The four groups included those with Alzheimer's disease (n = 28), parkinsonism with dementia (n = 10), progressive supranuclear palsy with dementia (n = 10), and dementia of vascular origin (n = 28). The results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Other alterations in the neuroendocrine system of AD patients have also been reported. An attenuated growth hormone-releasing hormone (GHRH) -induced growth hormone response specific to AD was demonstrated by Lesh et al (146) and Ghiso et al (147), but not by others (148,149). Furthermore, a reduction in CSF levels of antidiuretic hormone was observed not only in AD patients, but also in patients with frontal lobe dementia (150).…”
Section: Neuroendocrine Systemmentioning
confidence: 95%
“…Other alterations in the neuroendocrine system of AD patients have also been reported. An attenuated growth hormone-releasing hormone (GHRH) -induced growth hormone response specific to AD was demonstrated by Lesh et al (146) and Ghiso et al (147), but not by others (148,149). Furthermore, a reduction in CSF levels of antidiuretic hormone was observed not only in AD patients, but also in patients with frontal lobe dementia (150).…”
Section: Neuroendocrine Systemmentioning
confidence: 95%
“…Provocation test studies for GH have revealed controversial results. Gomez et al [19] reported no significant difference in GH levels between AD patients and controls when GH secretion is stimulated by GHRH. However, a lower GH response to GHRH in AD patients compared to controls was reported by Ghigo et al [18].…”
Section: Discussionmentioning
confidence: 99%
“…The results of several studies addressing this point show varied results [61,[65][66][67][68][69]: superimposable responses of GH to GHRH than responses in controls; a blunted GH to GHRH response in AD patients; higher GH concentrations in the morning; a greater increase of GH to GHRH in AD patients than in controls. In general, the investigations of GHreleasing stimulation tests, especially of GHRH in AD, are equivocal and in some cases contradictory [70][71][72].…”
Section: Growth Hormone Response To Stimuli In Alzheimer's Diseasementioning
confidence: 99%